Exploring cell-derived extracellular vesicles in peripheral blood and bone marrow of B-cell acute lymphoblastic leukemia pediatric patients: proof-of-concept study - Magalhães-Gama, Fábio; Malheiros Araújo Silvestrini, Marina; Neves, Juliana Costa Ferreira; Araújo, Nilberto Dias; Alves-Hanna, Fabíola Silva; Kerr, Marlon Wendell Athaydes; Carvalho, Maria Perpétuo Socorro Sampaio; Tarragô, Andréa Monteiro; Soares Pontes, Gemilson; Martins-Filho, Olindo Assis; Malheiro, Adriana; Teixeira-Carvalho, Andréa; et al. (Frontiers in Immunology, 2024)
Extracellular vesicles (EVs) are heterogeneous, phospholipid membrane enclosed particles that are secreted by healthy and cancerous cells. EVs are present in diverse biological fluids and have been associated with the severity of diseases, which indicates their potential as biomarkers for diagnosis, prognosis and as therapeutic targets. This study investigated the phenotypic characteristics of EVs derived from peripheral blood (PB) and bone marrow (BM) in pediatric patients with B-cell acute lymphoblastic leukemia (B-ALL) during different treatment stages. PB and BM plasma were collected from 20 B-ALL patients at three time points during induction therapy, referred to as: diagnosis baseline (D0), day 15 of induction therapy (D15) and the end of the induction therapy (D35). In addition, PB samples were collected from 10 healthy children at a single time point. The EVs were measured using CytoFLEX S flow cytometer. Calibration beads were employed to ensure accurate size analysis. The following, fluorescent-labeled specific cellular markers were used to label the EVs: Annexin-V (phosphatidylserine), CD235a (erythrocyte), CD41a (platelet), CD51 (endothelial cell), CD45 (leukocyte), CD66b (neutrophil), CD14 (monocyte), CD3 (T lymphocyte), CD19, CD34 and CD10 (B lymphoblast/leukemic blast). Our results demonstrate that B-ALL patients had a marked production of EV-CD51/61+, EV-CD10+, EV-CD19+ and EV-CD10+CD19+ (double-positive) with a decrease in EV-CD41a+ on D0. However, the kinetics and signature of production during induction therapy revealed a clear decline in EV-CD10+ and EV-CD19+, with an increase of EV-CD41a+ on D35. Furthermore, B-ALL patients showed a complex biological network, exhibiting distinct profiles on D0 and D35. Interestingly, fold change and ROC curve analysis demonstrated that EV-CD10+CD19+ were associated with B-ALL patients, exhibited excellent clinical performance and standing out as a potential diagnostic biomarker. In conclusion, our data indicate that EVs represent a promising field of investigation in B-ALL, offering the possibility of identifying potential biomarkers and therapeutic targets.